A new generalisation of Sam-Solai's multivariate additive gumbel min distribution. Issue 5 (3rd September 2017) - Jayakumar, G. S. David Sam; Solairaju, A.; Sulthan, A.
Abstract: The paper proposed a new generalization of bounded Continuous multivariate symmetric probability distributions. More specifically, a new generalization of Sam - Solai's Multivariate additive Gumbel Min distribution. Further, the authors find its Marginal, Multivariate Conditional distributions, Multivariate Generating functions, Multivariate survival, hazard functions and also discussed it's special cases which includes the transformation of Sam-Solai's Multivariate additive Gumbel Min distribution into Multivariate additive log - Gumbel Min distribution, Multivariate additive Gumbel max distribution. Moreover, the bivariate correlation between two Gumbel min variables and Co-variances were derived.